(untitled) (Baghdad Science Journal, 2010)
A new Schiff base of 4- flourophenyl-4- nitrobenzyliden (L) ,was prepared and used to prepare a number of metal complexes with Cr (III) , Fe (III), Co(II) ,Ni (II) and Cu (II). These complexes were isolated and characterized by (FITR),UV-Vis spectroscopy and flame atomic absorption techniques in addition to magnetic susceptibility, and conductivity measurements. The study of the nature of the complexes formed in ethanol was done following the molar ratio method gave results, agreed with those obtained from isolated solid state studies. The antibacterial activity for the ligand and its metal complexes were examined against two selected microorganisms, Pseudomonas aeruginosa and Staphylococcus aureus.The results indicated that the complexes show the enhanced activity in comparison to the free ligand; these were attributed to the synergetic effect between the metal ion and the ligand in addition to the difference in the structural varieties.